The relationship between early mobilization and the healing process of perineal wounds in post partum mothers - Simanjuntak, Lisda Yanti (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2022)
World Health Organization (WHO) 2017, about 830 women die every day due to complications during pregnancy or childbirth, to reduce the risk of maternal death globally from 216.1 million live births in 2015 to 70 per 100,000 live births. Perineal wound is a tear in the birth canal spontaneously or by episiotomy at the time of delivery of the fetus. The dangers and complications of perineal rupture include bleeding, infection, and dyspareunia (pain during sexual intercourse). Bleeding at perineal rupture can be severe especially in grades I and III ruptures or if the perineal rupture extends to the side or up the vulva on the clitoris. Based on an initial survey conducted by researchers at the Nabila Primary Clinic, Deli Serdang Regency on March 29, 2022. Out of 8 postpartum mothers, only 3 mothers did Early Mobilization, due to fear after childbirth. The purpose of this study was to determine the relationship between early mobilization and the perineal wound healing process in postpartum mothers at the Nabila Pratama Clinic in 2022. The research method used was observational with a cross-sectional survey analytic descriptive research type. The results of this Bivariate study indicate that the Chi-Square Statistical Test results obtained a P value of 0.021, then Ho is rejected and Ha is accepted, which means that there is a significant relationship between Early Mobilization and the Healing Process of Perineal Wounds in Post Partum Mothers.Abstrak: World Health Organization (WHO)  2017, sekitar 830 wanita meninggal setiap hari karena komplikasi selama hamil atau persalinan, Untuk mengurangi resiko kematian ibu secara global dari 216.100.000 kelahiran hidup pada tahun 2015 menjadi 70 per 100.000 kelahiran hidup. Luka perineum adalah sebagai adanya robekan jalan lahir secara spontan maupun secara episiotomi pada saat melahirkan janin. Bahaya dan komplikasi ruptur perineum antara lain perdarahan, infeksi, dan disparenia (nyeri selama berhubungan seksual). Perdarahan pada ruptur perineum dapat menjadi hebat khusunya pada ruptur derajat I dan III atau jika ruptur perineum meluas ke samping atau naik ke vulva mengenai klitoris. Berdasarkan survey awal yang dilakukan peneliti di Klinik Pratama Nabila Kabupaten Deli Serdang tanggal 29 Maret tahun 2022. Dari 8 ibu post partum hanya 3 ibu yang melakukan Mobilisasi Dini, disebabkan karena ketakutan pasca persalinan. Tujuan penelitian ini untuk mengetahui Untuk mengetahui hubungan mobilisasi dini terhadap proses penyembuhan luka perineum pada ibu post partum di Klinik Pratama Nabila Tahun 2022. Metode penelitian yang digunakan observasional dengan jenis penelitian deskriptif analitik survei cross secsional. Hasil penelitian Bivariat ini menunjukkan bahwa Dari hasil Uji Statistik Chi-Square diperoleh niali P value 0,021, maka Ho ditolak dan Ha diterima yang artinya ada hubungan signifikan antara Mobilisasi Dini Terhadap Prosese Penyembuhan Luka Perineum Pada Ibu Post Partum